Acute effects of dryland muscular endurance and maximum strength training on sprint swimming performance in young swimmers - Arsoniadis, G. G.; Botonis, P. G.; Bogdanis, G. C.; Terzis, G.; Toubekis, A. G. (Journal of Sports Sciences, 2024)
The study examined acute effects of dryland muscular endurance (ME) and maximum strength (MS) sessions on performance, physiological, and biomechanical variables during a subsequent sprint swimming session. Twenty-seven swimmers (16.5 ± 2.6 yrs) completed three experimental conditions including: i) ME, 55% of 1-repetition maximum, ii) MS, 90% of 1-repetition maximum, and iii) control (CON, no dry-land). Twenty minutes following ME, MS and CON sessions swimmers performed a 10-s tethered swimming sprint, four by 50-m (4 × 50-m), and a 100-m front crawl sprints. Performance time, blood lactate, heart rate (HR), stroke rate (SR), stroke length (SL), stroke index (SI), and stroke efficiency (EtaF) were measured during 4 × 50-m and 100-m. Hand grip strength (HG), and shoulder muscles isometric strength (ISO) were measured after each session. Mean 4 × 50-m time increased in ME compared to CON by 1.7 ± 2.7% (p = 0.01), while 100-m time was similar among conditions (p > 0.05). ISO was lower after dry-land training in all conditions (p = 0.01). Tethered force, HG, HR, SR, SL, SI, and EtaF were no different between conditions (p > 0.05). Dryland ME session decrease swimming performance; however, ME and MS sessions did not affect technical ability during a subsequent maximum intensity swimming.